The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s40267-022-00899-6
|View full text |Cite
|
Sign up to set email alerts
|

Peak months of pandemic’s first-wave in India: a cross-sectional assessment of knowledge, attitudes and practice towards COVID-19 among internet-savvy individuals

Abstract: Background A successful pandemic response in populated geographies and resource-limited settings like India relies on informed decision making. Knowledge, attitudes, and practices (KAP) studies performed during these times are crucial to illustrate how well a community adopts prevention strategies. Objective The present study, conducted during the peak months of the first wave of the COVID-19 pandemic, aimed at assessing the KAP levels of internet-savvy Indians. Methods This observational cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Research about gender and Covid-19 knowledge has returned conflicting findings. While Sultana et al (2022) reported that women scored higher on Covid-19 knowledge assessments in Bangladesh, Pinchoff et al (2020) found the opposite in India, and Marudachalam et al (2022) found no significant gender differences in the same country. Knowledge gap research that includes gender comparisons remains rare (Viswanath & Finnegan, 1996), and officials often fail to consider gendersensitive content and media that effectively target women (Anhang et al, 2004;Chhetri & Lepcha, 2022).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Research about gender and Covid-19 knowledge has returned conflicting findings. While Sultana et al (2022) reported that women scored higher on Covid-19 knowledge assessments in Bangladesh, Pinchoff et al (2020) found the opposite in India, and Marudachalam et al (2022) found no significant gender differences in the same country. Knowledge gap research that includes gender comparisons remains rare (Viswanath & Finnegan, 1996), and officials often fail to consider gendersensitive content and media that effectively target women (Anhang et al, 2004;Chhetri & Lepcha, 2022).…”
Section: Literature Reviewmentioning
confidence: 88%